Driven to Help: The Dynamics of Learning Motivation and Prosocial Behavior in Young Volunteers - Yeni Septiani; Yasin Syarif Hidayatullah (Manunggal Halim Jaya, 2026)
Volunteers in early adulthood are generally in the process of development, where they begin to learn to be independent, seek new experiences, and strengthen the social values they hold. During this period, the enthusiasm for learning and the interest in taking actions that benefit others tend to increase, along with a growing sense of responsibility toward society. Therefore, this study was conducted to determine the relationship between learning motivation and prosocial behavior in early adults who volunteer for social community activities at KL Lazismu Unisa Yogyakarta. The population in this study consisted of 150 individuals, with a sample of 108 students selected through purposive sampling techniques. The data collection instruments used in this study were Hardiyani's (2005) learning motivation scale and Mussen's (2002) prosocial behavior scale. Data analysis was conducted using the Kolmogorov-Smirnov normality test, linearity test, and Pearson correlation test Product moment using SPSS 21. The results of the study indicate that there is a positive and significant relationship between learning motivation and prosocial behavior (r = 0.842; p = 0.000). The higher the learning motivation an individual has, the more positive they will be in displaying prosocial behavior.